Do Faculty and Residents Agree on Obstetrics and Gynecology Surgical Training Needs?. (October 2016) - Braun, Kelli; Swift, Steven; Stepleman, Lara
Abstract : BACKGROUND: Surgical education is an essential, complex, component of residency training. Resident and faculty needs are important in guiding the educational agenda; studies demonstrate that these groups do not always agree on needs. METHODS: A 50-item needs assessment tool was administered during scheduled meetings at our single academic center to capture resident and faculty perceptions of the adequacy of our program's surgical training; all items were ranked on a 5-point agreement scale. Content domains included feedback, surgical preparation, intra-operative performance, simulation, and the Ob-Gyn Milestones procedures (we assessed satisfaction with training and the perceived helpfulness of simulation to improve performance of those procedures). RESULTS: Twelve surgical faculty (80%) and 13 residents (87%) completed the needs assessment; t tests compared resident/faculty group differences. Both groups agreed on the adequacy of surgical content domains, however, faculty consistently self-reported delivering feedback at a significantly higher level than residents' perceived receiving it ( P <.05). Both groups were least satisfied with training in cystotomy repair, breech vaginal delivery, and 3rd/4th-degree laceration repair. Both rated simulation in breech vaginal delivery and vaginal hysterectomy as most useful for improving performance. For all procedures, faculty consistently rated at significantly higher levels, simulation's usefulness to improve procedure performance. DISCUSSION: Although residents and faculty agree on areas needing most improvement, differences exist in perception of feedback and usefulness of simulation to improve performance.